ANALISIS INDIKATOR FUNDAMENTAL DAERAH DI KALIMANTAN BARAT: PERTUMBUHAN PENDUDUK DAN PERTUMBUHAN EKONOMI TAHUN 2019-2020 - Iva Ashari Ananda (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
In 2019, the population growth in the West Kalimantan region, according to data from the Central Statistics Agency, was 5,069,127 million people. In 2020, the population of West Kalimantan as of September 2020 is 5,414,350 million people. Development planning covers various comprehensive aspects, among others, population and economy. Population growth in West Kalimantan has increased from time to time. In terms of population growth, Pontianak City has the highest number of population, which is 658,685 thousand people with a percentage of 12.2%. This is due to the large number of people who move (migrate) from villages to cities in search of work. There was an increase in the labor force participation rate in 2020 which increased by 1.69% (yoy) compared to 2019. The labor force participation rate (TPAK) in West Kalimantan in 2019 was 68.30% and in 2020 it was 68.83%. This condition reflects the increase in the number of workers in West Kalimantan has not been fully balanced with absorption on the employment side (LU).